GA-Hecate antiviral properties on HCV whole cycle represent a new antiviral class and open the door for the development of broad spectrum antivirals - Batista, Mariana Nogueira [UNESP]; Silva Sanches, Paulo Ricardo da [UNESP]; Carneiro, Bruno Moreira [UNESP]; Silva Braga, Ana Claudia [UNESP]; Fernandes Campos, Guilherme Rodrigues [UNESP]; Chilli, Eduardo Maffud [UNESP]; Rahal, Paula [UNESP] (Nature Publishing Group, 2018)
In recent years, synthetic peptides have been considered promising targets for drug development that possess low side-effects, are cost-effective and are susceptible to rational design. Hecate was initially described as a potent bacterial inhibitor and subsequently as an anticancer drug with functions related to its lipid interaction property. Viruses, such as hepatitis C virus (HCV), have a lipid-dependent life cycle and could be affected by Hecate in many ways. Here, we assessed modifications on Hecate's N-terminus region and its effects on HCV and hepatotoxicity. Gallic acid-conjugated Hecate was the most efficient Hecate-derivative, presenting high potential as an antiviral and inhibiting between 50 to 99% of all major steps within the HCV infectious cycle. However, the most promising aspect was GA-Hecate's mechanism of action, which was associated with a balanced lipid interaction with the viral envelope and lipid droplets, as well as dsRNA intercalation, allowing for the possibility to affect other ssRNA viruses and those with a lipid-dependent cycle.